2017
DOI: 10.1039/c7cp00836h
|View full text |Cite
|
Sign up to set email alerts
|

Pair natural orbital and canonical coupled cluster reaction enthalpies involving light to heavy alkali and alkaline earth metals: the importance of sub-valence correlation

Abstract: In this work, we tested canonical and domain based pair natural orbital coupled cluster methods (CCSD(T) and DLPNO-CCSD(T), respectively) for a set of 32 ligand exchange and association/dissociation reaction enthalpies involving ionic complexes of Li, Be, Na, Mg, Ca, Sr, Ba and Pb(ii). Two strategies were investigated: in the former, only valence electrons were included in the correlation treatment, giving rise to the computationally very efficient FC (frozen core) approach; in the latter, all non-ECP electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 75 publications
6
71
0
Order By: Relevance
“…Most of the structures accounted are closed‐shell singlets with HOMO–LUMO gap sufficiently large to use NormalPNO cutoffs in ORCA. However, neutral X is a doublet with quite small HOMO–LUMO gap; hence, we used UHF wavefunction with TightPNO cutoffs for electron affinity determination . That choice is confirmed with the results of test computations collected in Table .…”
Section: Introductionsupporting
confidence: 58%
“…Most of the structures accounted are closed‐shell singlets with HOMO–LUMO gap sufficiently large to use NormalPNO cutoffs in ORCA. However, neutral X is a doublet with quite small HOMO–LUMO gap; hence, we used UHF wavefunction with TightPNO cutoffs for electron affinity determination . That choice is confirmed with the results of test computations collected in Table .…”
Section: Introductionsupporting
confidence: 58%
“…[93,94] For this cluster size, one can furthermore use canonical, 2 nd -order Møller-Plesset perturbation theory (MP2) with the def2-TZVPP basis set. Additionally, non-canonical coupled cluster methods such as the DLPNO-CCSD(T) approach [95][96][97][98] can be used employing the def2-TZVPP basis set as implemented in the Orca program.…”
Section: Resultsmentioning
confidence: 99%
“…Single points were also performed with the hybrid functionals PBE0-D3 [108] , B3LYP-D3 [126][127] and M06 [109] and Møller-Plesset second order perturbation theory MP2 [128][129][130] in Turbomole all with the def2-TZVPP/def2-QZVPP basis sets and a corresponding auxiliary basis set [131][132][133] . For CCSD(T) [129][130] both Turbomole and Orca program packages were used, Turbomole for canonical CCSD(T) calculations and Orca [93][94] to compare the accuracy of the DLPNO approximation [97][98] with the canonical values obtained for the smallest cluster model T1. Then, DLPNO CCSD(T) was carried out for the largest cluster and canonical CCSD for T1 with cc-pVXZ [134] (X=D, T, Q) basis-sets, for complete basis-set limit extrapolation (CBS) [98,[101][102]135] (details on the equations used available in the SI).…”
Section: Methodsmentioning
confidence: 99%
“…In 1986, Bauschlicher et al noted that the (m1)sp outer core electrons should be correlated to obtain useful results for the alkali and alkaline-earth monohydroxides, 69 with a similar finding noted more recently by Neese and co-workers. 70 Iron et al also observed that neglecting to correlate the 3s3p for small K and Ca compounds leads "to erratic results at best." 71 This effect goes beyond that expected simply due to core-core and core-valence correlation, as in a number of cases, molecular orbitals formed as a linear combination of outer-core orbitals from the metal with valence orbitals from the heteroatom are treated as (frozen-) core orbitals in the post-HF calculation.…”
Section: Valence Correlationmentioning
confidence: 99%